Algal biomass energy carriers as fuels: An alternative green source. Issue 2 (April 2017) - Arvindnarayan, Sundaram; Sivagnana Prabhu, Kandasamy K.; Shobana, Sutha; Dharmaraja, Jeyaprakash; Pasupathy, A.
Abstract: In this study, biomass and lipid productivity of an alga namely Botryococcus braunii at dissimilar nitrogen cultural environment was observed. In addition, the transesterification of algal feed stock with absolute ethanol medium in the presence of Ni catalyst with hydrogen environment and Ni(II)-Schiff base chelate as promoter was carried out to yield more algal oil as the catalyst along with promoter possesses high specific surface area, strong base strength and high base site concentration. The synthesized Schiff base and its Ni(II)-Schiff base chelate were characterized by micro elemental, spectral, thermal and XRD/SEM analyses. The quality of the extracted algal oil was analyzed using ultimate, analytical and spectral studies. In engine performance test, the algal oil–diesel blends showed a slight increase in specific fuel consumption with lower brake power. The green gas emissions were reduced for all the tested blends except (NO)x . Moreover, in vitro antimicrobial and antioxidant activities of the algal oil extracted from the alga of dissimilar nitrogen cultural environment were studied and the results obtained show remarkable activity. Graphical abstract: Biomass and lipid productivity of an alga namely Botryococcus braunii at dissimilar nitrogen cultural environment was observed. In addition, the transesterification of algal feed stock with absolute ethanol medium in the presence of Ni catalyst with hydrogen environment and Ni(II)-Schiff base chelate as promoter was carried out. In engine performance test, the algal oil–diesel blends showed a slight increase in specific fuel consumption with lower brake power. The green gas emissions were reduced for all the tested blends except (NO)x . Moreover, in vitro antimicrobial and antioxidant activities of the algal oil extracted from the alga of dissimilar nitrogen cultural environment were studied and the results obtained show remarkable activity. Highlights: Low viscous algal oil was produced using Ni catalyst with hydrogen environment and Ni(II)-Schiff base chelate as promoter. Algal oil–diesel blends showed a slight increase in specific fuel consumption with lower brake power. Green gas emissions were reduced for all the tested blends except (NO)x . Algal oils show remarkable in vitro antimicrobial and antioxidant activities. B10 and B50 blend fuels are biodegradable and prevent the global warming.